The global prevalence of native and non-native plants in urban areas - Andressa L.L. Luna; Renata Trevizan; Camila Bosenbecker; Victor H.D. Silva; Ingrid N. Gomes; Carlos A. Ordóñez-Parra; Bruna Nascimento; Pedro A. Anselmo; Flávia S. Faria; Teresa M. Fonseca; Ricardo R.C. Solar; Tatiana G. Cornelissen; et al. (Landscape and Urban Planning, 2026)

Quantifying leaf herbivory: A guide to methodological trade‐offs and best practices - Tatiana Cornelissen; Gisele M. Mendes; Fernando A. O. Silveira; Wesley Dáttilo; Roger Guevara; Ramiro Aguilar; Maria Gabriela Boaventura; Ricardo Campos; Ek del Val; Guilherme Ramos Demetrio; Marcilio Fagundes; Rafael de Paiva Farias; et al. (Ecology, 2026)
Leaf herbivory is a ubiquitous ecological interaction that varies significantly in intensity across species, habitats, and biogeographic regions. Although quantification of leaf damage is crucial for understanding many ecological processes, the accuracy and precision of various damage estimation methods used by researchers, including visual estimation, digital image analysis, and artificial intelligence, have not been evaluated and compared. We use a phylogenetically diverse group of tropical plants to compare the accuracy and precision of damage estimation methods and use the results to provide a guide to herbivory estimation that balances the advantages and disadvantages of each method. We found that visual estimation tended to overestimate herbivory levels compared to digital methods but was 15 times faster and improved in accuracy and speed with training. Conversely, deep‐learning algorithms underestimated herbivory relative to image analysis with ImageJ when it was on the margin, but showed similar accuracy for damage inside of leaf margins. Our results indicate that while visual methods allow for rapid assessment of large sample sizes and are suitable for detecting broad patterns of damage, image analysis is crucial for accurate and precise quantification. The disadvantages of each method, however, can be minimized through proper training and efficient use of each tool, and we therefore provide a guide of practical approaches to herbivory estimation.

Design of an efficient constructed wetland prototype for sustainable wastewater treatment in developing countries: A community case study in Mexico - Dagoberto Ruiz; Sergio A. Gamboa; Laura A. Paniagua-Solar; Nallely Téllez; Teresa Zayas (Journal of Water Process Engineering, 2025)

A systematic review of the land use change effects on ant diversity in Neotropics - Icaro Wilker; Antônio C.M. Queiroz; Carla R. Ribas; Maria Santina C. Morini; Chaim J. Lasmar; Fernando A. Schmidt; Rodrigo M. Feitosa; Anselmo Nogueira; Fabrício B. Baccaro; Mônica A. Ulysséa; Thiago Izzo; Lucas N. Paolucci; et al. (Biological Conservation, 2024)

Ants of Brazil: an overview based on 50 years of diversity studies - Rodrigo M. Feitosa; Gabriela P. Camacho; Thiago S. R. Silva; Mônica A. Ulysséa; Natalia Ladino; Aline M. Oliveira; Emília Z. Albuquerque; Fernando A. Schmidt; Carla R. Ribas; Anselmo Nogueira; Fabrício B. Baccaro; Antônio C. M. Queiroz; et al. (Systematics and Biodiversity, 2022)

Ant diversity studies in Brazil: an overview of the myrmecological research in a megadiverse country - F. A. Schmidt; C. R. Ribas; R. M. Feitosa; F. B. Baccaro; A. C. M. de Queiroz; T. G. Sobrinho; Y. Quinet; K. S. Carvalho; T. Izzo; M. S. de Castro Morini; A. Nogueira; H. M. Torezan-Silingardi; et al. (Insectes Sociaux, 2022)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

How much leaf area do insects eat? A data set of insect herbivory sampled globally with a standardized protocol - Gisele M. Mendes; Fernando A. O. Silveira; Carolina Oliveira; Wesley Dáttilo; Roger Guevara; Betsabé Ruiz‐Guerra; Maria Gabriela Boaventura; Sershen; Syd Ramdhani; Shyam S. Phartyal; Sérvio P. Ribeiro; Victor Diniz Pinto; et al. (Ecology, 2021)
Herbivory is ubiquitous. Despite being a potential driver of plant distribution and performance, herbivory remains largely undocumented. Some early attempts have been made to review, globally, how much leaf area is removed through insect feeding. Kozlov et al., in one of the most comprehensive reviews regarding global patterns of herbivory, have compiled published studies regarding foliar removal and sampled data on global herbivory levels using a standardized protocol. However, in the review by Kozlov et al., only 15 sampling sites, comprising 33 plant species, were evaluated in tropical areas around the globe. In Brazil, which ranks first in terms of plant biodiversity, with a total of 46,097 species, almost half (43%) being endemic, a single data point was sampled, covering only two plant species. In an attempt to increase knowledge regarding herbivory in tropical plant species and to provide the raw data needed to test general hypotheses related to plant–herbivore interactions across large spatial scales, we proposed a joint, collaborative network to evaluate tropical herbivory. This network allowed us to update and expand the data on insect herbivory in tropical and temperate plant species. Our data set, collected with a standardized protocol, covers 45 sampling sites from nine countries and includes leaf herbivory measurements of 57,239 leaves from 209 species of vascular plants belonging to 65 families from tropical and temperate regions. They expand previous data sets by including a total of 32 sampling sites from tropical areas around the globe, comprising 152 species, 146 of them being sampled in Brazil. For temperate areas, it includes 13 sampling sites, comprising 59 species. Thus, when compared to the most recent comprehensive review of insect herbivory (Kozlov et al.), our data set has increased the base of available data for the tropical plants more than 460% (from 33 to 152 species) and the Brazilian sampling was increased 7,300% (from 2 to 146 species). Data on precise levels of herbivory are presented for more than 57,000 leaves worldwide. There are no copyright restrictions. Please cite this paper when using the current data in publications; the authors request to be informed how the data is used in the publications.

Second rate or a second chance? Assessing biomass and biodiversity recovery in regenerating Amazonian forests - Gareth D. Lennox; Toby A. Gardner; James R. Thomson; Joice Ferreira; Erika Berenguer; Alexander C. Lees; Ralph Mac Nally; Luiz E. O. C. Aragão; Silvio F. B. Ferraz; Julio Louzada; Nárgila G. Moura; Victor H. F. Oliveira; et al. (Global Change Biology, 2018)
Secondary forests (SFs) regenerating on previously deforested land account for large, expanding areas of tropical forest cover. Given that tropical forests rank among Earth’s most important reservoirs of carbon and biodiversity, SFs play an increasingly pivotal role in the carbon cycle and as potential habitat for forest biota. Nevertheless, their capacity to regain the biotic attributes of undisturbed primary forests (UPFs) remains poorly understood. Here, we provide a comprehensive assessment of SF recovery, using extensive tropical biodiversity, biomass, and environmental datasets. These data, collected in 59 naturally regenerating SFs and 30 co‐located UPFs in the eastern Amazon, cover >1,600 large‐ and small‐stemmed plant, bird, and dung beetles species and a suite of forest structure, landscape context, and topoedaphic predictors. After up to 40 years of regeneration, the SFs we surveyed showed a high degree of biodiversity resilience, recovering, on average among taxa, 88% and 85% mean UPF species richness and composition, respectively. Across the first 20 years of succession, the period for which we have accurate SF age data, biomass recovered at 1.2% per year, equivalent to a carbon uptake rate of 2.25 Mg/ha per year, while, on average, species richness and composition recovered at 2.6% and 2.3% per year, respectively. For all taxonomic groups, biomass was strongly associated with SF species distributions. However, other variables describing habitat complexity—canopy cover and understory stem density—were equally important occurrence predictors for most taxa. Species responses to biomass revealed a successional transition at approximately 75 Mg/ha, marking the influx of high‐conservation‐value forest species. Overall, our results show that naturally regenerating SFs can accumulate substantial amounts of carbon and support many forest species. However, given that the surveyed SFs failed to return to a typical UPF state, SFs are not substitutes for UPFs.

The deadly route to collapse and the uncertain fate of Brazilian rupestrian grasslands - G. Wilson Fernandes; N. P. U. Barbosa; B. Alberton; A. Barbieri; R. Dirzo; F. Goulart; T. J. Guerra; L. P. C. Morellato; R. R. C. Solar (Biodiversity and Conservation, 2018)

How pervasive is biotic homogenization in human‐modified tropical forest landscapes? - Ricardo Ribeiro de Castro Solar; Jos Barlow; Joice Ferreira; Erika Berenguer; Alexander C. Lees; James R. Thomson; Júlio Louzada; Márcia Maués; Nárgila G. Moura; Victor H. F. Oliveira; Júlio C. M. Chaul; José Henrique Schoereder; et al. (Ecology Letters, 2015)
Land‐cover change and ecosystem degradation may lead to biotic homogenization, yet our understanding of this phenomenon over large spatial scales and different biotic groups remains weak. We used a multi‐taxa dataset from 335 sites and 36 heterogeneous landscapes in the Brazilian Amazon to examine the potential for landscape‐scale processes to modulate the cumulative effects of local disturbances. Biotic homogenization was high in production areas but much less in disturbed and regenerating forests, where high levels of among‐site and among‐landscape β‐diversity appeared to attenuate species loss at larger scales. We found consistently high levels of β‐diversity among landscapes for all land cover classes, providing support for landscape‐scale divergence in species composition. Our findings support concerns that β‐diversity has been underestimated as a driver of biodiversity change and underscore the importance of maintaining a distributed network of reserves, including remaining areas of undisturbed primary forest, but also disturbed and regenerating forests, to conserve regional biota.

Erratum to: A multidisciplinary approach to enhance the conservation and use of hazelnut Corylus avellana L. genetic resources - L. Bacchetta; M. Rovira; C. Tronci; M. Aramini; P. Drogoudi; A. P. Silva; A. Solar; D. Avanzato; R. Botta; N. Valentini; P. Boccacci (Genetic Resources and Crop Evolution, 2015)

A multidisciplinary approach to enhance the conservation and use of hazelnut Corylus avellana L. genetic resources - L. Bacchetta; M. Rovira; C. Tronci; M. Aramini; P. Drogoudi; A. P. Silva; A. Solar; D. Avanzato; R. Botta; N. Valentini; P. Boccacci (Genetic Resources and Crop Evolution, 2015)

Molecular and morphological diversity of on-farm hazelnut (Corylus avellana L.) landraces from southern Europe and their role in the origin and diffusion of cultivated germplasm - P. Boccacci; M. Aramini; N. Valentini; L. Bacchetta; M. Rovira; P. Drogoudi; A. P. Silva; A. Solar; F. Calizzano; V. Erdoğan; V. Cristofori; L. F. Ciarmiello; et al. (Tree Genetics & Genomes, 2013)

Fatty acids and alpha-tocopherol composition in hazelnut (Corylus avellana L.): a chemometric approach to emphasize the quality of European germplasm - L. Bacchetta; M. Aramini; A. Zini; V. Di Giammatteo; D. Spera; P. Drogoudi; M. Rovira; A. P. Silva; A. Solar; R. Botta (Euphytica, 2013)

Can ants be used as indicators of environmental impacts caused by arsenic? - Carla R. Ribas; Ricardo R. C. Solar; Renata B. F. Campos; Fernando A. Schmidt; Clarisse L. Valentim; José H. Schoereder (Journal of Insect Conservation, 2012)

Assessment of infection with polyomaviruses BKV, JCV and SV40 in different groups of Cuban individuals - Pedro A. Martínez; Vivian Kourí; Gustavo Cordero; Consuelo Correa; Yudira Soto; Virginia Capó; Licet González; Bienvenido Grá; Gregorio Petirena; César Silvério; Norma Hondal; Mabel González; et al. (Archives of Virology, 2012)

Hypogaeic pitfall traps: methodological advances and remarks to improve the sampling of a hidden ant fauna - F. A. Schmidt; R. R. C. Solar (Insectes Sociaux, 2010)

Phenotypic and Genotypic Diversity of European Chestnut (Castanea sativa Mill.) in Slovenia – Opportunity for Genetic Improvement - A. Solar; A. Podjavoršek; F. S. Štampar (Genetic Resources and Crop Evolution, 2005)

Radiolytic Degradation of the Herbicide Dicamba for Environmental Protection - P. Drzewicz; P. Gehringer; A. Bojanowska-Czajka; R. Zona; S. Solar; G. Nałcz-Jawecki; J. Sawicki; M. Trojanowicz (Archives of Environmental Contamination and Toxicology, 2005)

Flavonols of leaves in relation to apple scab resistance - V. Usenik; M. Mikuli-Petkovšek; A. Solar; F. Štampar (Journal of Plant Diseases and Protection, 2004)